Efek Infusa Daun Kunyit terhadap Kematian Larva Nyamuk Aedes Aegypti Instar III - Rahma Triyana; Heru Herbianto; Muhammad Ivan; Melya Susanti; Prima Adelin; Yuni Handayani; Ruhsyahadati Ruhsyahadati; Rifkind Malik (Universitas Malahayati Lampung, 2023)
ABSTRACT The Aedes mosquito causes nearly 390 million people to be infected each year. Handling of dengue can be carried out by eradicating Aedes aegypti mosquito larvae through the application of insecticides and Turmeric which has the potential as a natural larvicide. The aim of this study was to determine the effect of turmeric leaf infusion on the mortality of Aedes aegypti mosquito larvae. The scope of this study covers the field of parasitology, especially the entomology section. This study was conducted in February 2020 - March 2020 at the Biomedical Laboratory of Baiturahmah University. The type of research used was experimental through the Post Test Only Control Group Design method. The affordable population in this study were 3rd instar larvae of Aedes aegypti obtained from colonization results at the Health Entomology Laboratory, Faculty of Veterinary Medicine, Bogor Agricultural University (f.140), the total sample required was 420 larvae, data analysis used the kruskall-wallis test and probit test. Based on the research results, after giving 1%, 2%, 4%, 8% and 16% concentration of turmeric leaf infusion in 1, 2, 3, 4 and 24 hours there was no mortality of Aedes Aegypti larvae or 0%, after giving the leaf infusion concentration turmeric by 30% in 1, 2, 3 and 24 hours, the mortality of Aedes Aegypti larvae is 2.5%, after giving the concentration of turmeric leaf infusion of 50% in 1, 2, 3 and 24 hours, the mortality of Aedes Aegypti larvae is 1, 25%, after giving the concentration of turmeric leaf infusion of 60% within 1, 2, 3 and 24 hours, the mortality of Aedes Aegypti larvae is 6.25%, after giving the concentration of turmeric leaf infusion of 100% within 1, 2, 3 and 24 The mortality of Aedes Aegypti larvae is 8.5%, after giving a 100% concentration of turmeric leaf infusion within 1, 2, 3 and 24 hours, the mortality of Aedes Aegypti larvae is 17.5%, there is a comparison of the effectiveness of larvicides between turmeric leaf infusion and larvicide commercial (abate). sig 0.003 0.05 and the average mortality rate of Aedes aegypti larvae at all concentrations of turmeric leaves (100%, 80%, 60%, 50% and 30%) had a significant difference with positive control (abate) (p 0, 05) and the probit results show that the LC50 value of the larvicide infusion of turmeric leaves is 169.281 with intervals of 125.889 and 1822.476 and the LC99 value of the larvicide infusion of turmeric leaves is 573.233 with an interval of 252.901 to 673585.866 and a very potent concentration of killing Aedes aegypti larvae is 100% with an average lethal rate of Aedes aegypti mosquito larvae, namely 3.5. There is a comparison of larvicide effectiveness between turmeric leaf infusion and commercial larvicide (abate). sig 0,000 0.05. Keywords: Aedes Aegypti Larvae, Turmeric Leaf Infusion, LC 50, LC 99 ABSTRAK Nyamuk Aedes mengakibatkan nyaris 390 juta orang terinfeksi tiap tahunnya, Penanganan DBD mampu dilaksanakan melalui cara membasmi larva nyamuk Aedes aegypti melalui pemberian insektisida dan Kunyit yang berpotensi sebagai larvasida alami.Tujuan penelitian untuk mengetahui efek infusa daun kunyit terhadap kematian larva nyamuk Aedes aegypti. Penelitian ini mencakup bidang ilmu Parasitologi khususnya bagian Entomologi. Penelitian dilaksanakan pada februari – maret 2020 di Laboratorium Biomedik Universitas Baiturahmah Padang. Jenis penelitian yang digunakan ialah Eksperimental melalui metode Post Test Only Control Grup Design. Populasi terjangkau penelitian ini adalah larva Aedes aegypti instar III yang di dapat dari hasil kolonisasi di Laboratorium Entomologi Kesehatan Fakultas Kedokteran Hewan Institut Pertanian Bogor (f.140), total sampel yang dibutuhkan adalah 420 ekor larva, analisa data menggunakan uji kruskall-wallis dan uji probit. Berdasarkan hasil penelitian, setelah pemberian konsentrasi infusa daun kunyit sebesar 1%, 2%, 4%, 8% dan 16% dalam waktu 1, 2, 3, 4 dan 24 jam tidak ada mortalitas larva Aedes Aegypti atau 0%, setelah pemberian konsentrasi infusa daun kunyit sebesar 30% dalam waktu 1, 2, 3 dan 24 jam mortalitas larva Aedes Aegypti adalah 2,5%, setelah pemberian konsentrasi infusa daun kunyit sebesar 50% dalam waktu 1, 2, 3 dan 24 jam mortalitas larva Aedes Aegypti adalah 1,25%, setelah pemberian konsentrasi infusa daun kunyit sebesar 60% dalam waktu 1, 2, 3 dan 24 jam mortalitas larva Aedes Aegypti adalah 6,25%, setelah pemberian konsentrasi infusa daun kunyit sebesar 100% dalam waktu 1, 2, 3 dan 24 jam mortalitas larva Aedes Aegypti adalah 8,5%, setelah pemberian konsentrasi infusa daun kunyit sebesar 100% dalam waktu 1, 2, 3 dan 24 jam mortalitas larva Aedes Aegypti adalah 17,5%, dan rata-rata kematian larva Aedes aegypti pada seluruh konsentrasi daun kunyit (100%, 80%, 60%, 50% dan 30%) memiliki perbedaan yang signifikan dengan kontrol positif (abate) (p0,05) dan hasil probit menunjukkan nilai LC50 dari larvasida infusa daun kunyit adalah 169,281 dengan interval 125,889 dan 1822,476 dan nilai LC99 dari larvasida infusa daun kunyit adalah 573,233 dengan interval 252,901 sampai 673585,866 serta konsentrasi yang amat ampuh mematikan larva nyamuk Aedes aegypti adalah 100% dengan rata-rata mematikan larva nyamuk Aedes aegypti yakni 3,5. Terdapat perbandingan efektivitas larvasida antara infusa daun kunyit dengan larvasida komersil (abate). sig 0,000 0,05. Kata Kunci: Larva Aedes Aegypti, Infusa Daun Kunyit, LC 50, LC 99